Fiduciary Duties and Equity-debtholder Conflicts - Becker, Bo; Strömberg, Per (Review of Financial Studies, 2012)
We use an important legal event to examine the effect of managerial fiduciary duties on equity-debt conflicts. A 1991 legal ruling changed corporate directors' fiduciary duties in Delaware firms, limiting managers' incentives to take actions that favor equity over debt for distressed firms. After this, affected firms responded by increasing equity issues and investment and by reducing risk. The ruling was also followed by an increase in leverage, reduced reliance on covenants, and higher values. Fiduciary duties appear to affect equity-bondholder conflicts in a way that is economically important, has impact on ex ante capital structure choices, and affects welfare. The Author 2012. Published by Oxford University Press on behalf of The Society for Financial Studies. All rights reserved. For Permissions, please e-mail: journals.permissions@oup.com., Oxford University Press.